1991
DOI: 10.1177/030631291021003002
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnology in the Twentieth Century

Abstract: Why has the term `biotechnology' been so ambiguous, while hopes for the subject have been so high? Exploring biotechnology's historic role as a `boundary object' between engineering and biology offers an explanation. The word is shown to have been interpreted in a variety of ways since the beginning of the century. Here the translations and negotiations over its identity are uncovered, showing that the words Biotechnik and Biotechnologie were poineered around World War I, principally in Denmark, Germany and Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 29 publications
0
16
0
3
Order By: Relevance
“…This now classical concept has proved extremely inspiring for science and technology studies scholars, eliciting a large body of studies, to the extent that ‘it might even be seen as itself something of a boundary object bridging different approaches’ in the field (Sismondo 2004: 148). Thus, it has provided insights regarding co‐ordination issues between different social worlds (Carter and Michael 2003), the changing shape of some objects, such as atherosclerosis (Mol 2002), in different settings, and the failure or the success of some innovations (Novek 2002, Bud 1991), according to whether they could be enacted as boundary objects or not. Further theoretical developments followed two distinct strands and gave birth to a host of related concepts.…”
Section: Introductionmentioning
confidence: 99%
“…This now classical concept has proved extremely inspiring for science and technology studies scholars, eliciting a large body of studies, to the extent that ‘it might even be seen as itself something of a boundary object bridging different approaches’ in the field (Sismondo 2004: 148). Thus, it has provided insights regarding co‐ordination issues between different social worlds (Carter and Michael 2003), the changing shape of some objects, such as atherosclerosis (Mol 2002), in different settings, and the failure or the success of some innovations (Novek 2002, Bud 1991), according to whether they could be enacted as boundary objects or not. Further theoretical developments followed two distinct strands and gave birth to a host of related concepts.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, shortly after Star and Griesemer (1989) initially proposed the concept of boundary objects, Bud (1991) observed that the term "biotechnology" serves as a boundary object between biology and engineering domains. He noted that while the meaning of the term was highly ambiguous, the innovative conceptual linkages that emerged surrounding it led to a range of new interdisciplinary approaches.…”
Section: Emergence Of Boundary Conceptsmentioning
confidence: 99%
“…Case studies of the creation and use of boundary objects abound in the literature (e.g., Harvey and Chrisman, 1998;Bud, 1991;Balmer, 1996;Henderson, 1991;Frost et al, 2002). The boundary object concept has even been applied to organic compost.…”
Section: Boundary Objectsmentioning
confidence: 99%